Spontaneous and post-interventional regression of cervical HPV infection - Procházka, Viktor; Skopelidou, Valeria; Romanová, Martina; Klát, Jaroslav (Ceska gynekologie, 2024)
Recent literature sources suggest that 15-20% of all malignant diseases have a viral aetiology. About 5% of these are caused by the human papillomavirus. The presence of papillomavirus is one of the strongest risk factors for development of a cervical pre-cancerous lesion and subsequent cervical cancer. The presented review provides a brief summary and characterisation of risk factors that influence spontaneous and post-interventional regression and persistence of papillomavirus in the cervical area.
Keywords: Papillomavirus Infections; dysplazie děložního hrdla; nádory děložního čípku; rizikové faktory; Uterine Cervical Neoplasms; Remission, Spontaneous; spontánní remise; lidé; Female; papillomavirus; ženské pohlaví; Risk Factors; conisation; Humans; Uterine Cervical Dysplasia; cervical cancer; cervical dysplasia; infekce papilomavirem